A combined data and power management infrastructure : for small satellites - Eickhoff, Jens (Springer Aerospace Technology, 2013)
In 2009 the need for a suitable onboard computer design arose for the small satellite project at the Institute of Space Systems, University of Stuttgart, Germany. It had to meet the constraints imposed by the small satellite (a 130 kg CubeSat) with its full featured ACS, diverse payloads and full CCSDS telecommand and telemetry standard compliance. The design of the Onboard Computer system lead to a functional merging between onboard computer components and the satellite's Power Control and Distribution Unit, resulting in a very innovative solution - the so-called Combined Data and Power Management Infrastructure. The technical implementation of such a design was achieved with the support of an international industry partner consortium consisting of Astrium GmbH, Aeroflex Colorado Springs Inc., 4Links Ltd., Aeroflex Gaisler AB, Vectronic Aerospace GmbH and HEMA Kabeltechnik GmbH & Co. KG. At end of the flight unit's development the consortium decided to provide a single consistent documentation of the developed CDPI Infrastructure. The technical overview should be available for other university students in a sort of mix between technical brochure and user guide. This book also might be of interest for future university or industry partners who intend to order rebuilds / adaptations of the CDPI infrastructure or even the entire satellite bus in Stuttgart for their missions.